Insecure-Anxious Attachment and Social Loneliness: The Mediating Roles of Income Security and Financial Well-Being - Dewi Khornida Marheni; Della Febrianti; Candy Candy; Cynthia Anna Wijayanti (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to analyze the effect of insecure-anxious attachment on social loneliness, with income security and financial well-being as mediating variables.Research Methodology: This study employs a quantitative research approach, with questionnaires distributed to 400 respondents from Generations X, Y, and Z in Batam City using purposive sampling, supported by interview insights, and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM).Results: The findings indicate that insecure-anxious attachment has a significant negative effect on income security and financial well-being, which in turn negatively affect social loneliness. Although insecure-anxious attachment has no direct effect on social loneliness, both financial variables fully mediate the relationship.Conclusions: Financial factors play a crucial mediating role in linking psychological attachment and social loneliness.|Limitations: This study is limited to respondents in Batam City and only examines income security and financial well-being as mediating variables. Other potential factors influencing social loneliness were not included in the research model.Contributions: This study advances the application of Attachment Theory and Self-Determination Theory by showing that insecure-anxious attachment is associated with social loneliness indirectly through income security and financial well-being rather than through a direct pathway. By integrating psychological and financial perspectives, the study positions financial conditions as mechanisms linking attachment-related insecurity to social disconnection, extending the application of both theories to the intersection of psychological, financial, and social experiences.